FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU MEROKOK DI MTS NEGERI 01 KOTA LUBUKLINGGAU - Santoso Ujang Effendi; Susilo Wulan; Fitratul Wahyuni (Universitas Pahlawan, 2020)
Health development is starting to face a new pattern of disease, which is an increase in cases of non-communicable diseases triggered by changes in people's lifestyles including cigarette consumption, whose prevalence continues to increase. This study aimed to study the factors associated with smoking behavior in students in MTS Negeri 01 Lubuklinggau City. This type of research was Analytic Survey and Cross Sectional research design. The population of this study was all male students of VII and VIII class in MTS Negeri 01 Lubuklinggau City in the 2018/2019 school year totaling 333 students. The sampling technique in this study used Proportional Random Sampling to obtain a sample of 77 students. The analysis in this study used univariate analysis and bivariate analysis. Bivariate analysis used Chi-Square test (χ2). To determine closeness of relationship used Contingency Coefficient (C) test. The results showed that of 77 students, there were 33 students (42.9%) who lacked knowledge, 45 students (58.4%) who were supportive of smoking behavior, 43 students (55.8%) who had their peers who supported smoking, and 46 students (59.7%) who behaved smoking. The results of bivariate analysis showed that there was a significant relationship between students' knowledge, students's attitudes, and students’s peers with smoking behavior of students in MTS Negeri 01, Lubuklinggau City with a moderate relationship category. Keywords: attitude, knowledge, peers, smoking behavior, student